Entrepreneurial Applications of Augmented Reality in Product Placement on Shelves - Farhansyah, Nadhif Haikal; Fabroyir, Hadziq (Pandawan, 2026)
A Planogram automation system has been developed to maximize the effectiveness of product arrangements on store shelves. However, its design could not be used at its full potential because of human errors that frequently occur when employees attempt to place products according to a predetermined planogram. These errors reduce both accuracy and efficiency in the implementation process. Previous research addressed this challenge by proposing solutions in the form of automatic planogram compliance supervisors that utilize object detection technology to detect deviations. In contrast, this work proposed another approach to minimize human errors, namely by developing a real-time guidance system for product placement on the shelves using an Augmented Reality (AR) platform. Two different AR devices were implemented, consisting of a handheld Samsung Galaxy Tab S7 and a Video See Through (VST), Head Mounted Display (HMD) using Meta Quest 3, and their performance was compared to the conventional paper-based method. The system was evaluated through a user study involving 11 participants who had prior experience in product placement but no experience with HMD devices. Results showed that paper instruction achieved the best completion time in task performance, while no significant differences were found in error performance. HMD and paper instruction demonstrated similar outcomes on cognitive load, whereas handheld AR showed the worst performance and physical demand. Based on these results and post-task feedback, it can be concluded that although paper instruction remained the most favored method, the HMD demonstrated the greatest potential for future product placement guidance systems.